Discovery, synthesis and biological characterization of a series of N-(1-(1, 1-dioxidotetrahydrothiophen-3-yl)-3-methyl-1H-pyrazol-5-yl)acetamide ethers as novel GIRK1/2 potassium channel activators. Issue 8 (21st June 2021) - Sharma, Swagat; Lesiak, Lauren; Aretz, Christopher D.; Du, Yu; Kumar, Sushil; Gautam, Nagsen; Alnouti, Yazen; Dhuria, Nikilesh V.; Chhonker, Yashpal S.; Weaver, C. David; Hopkins, Corey R.
Abstract : We report the synthesis, biological characterization, and in vitro PK properties of a new ether series of compounds that incorporate the sulfone group while maintaining potency and stability. 11a was identified as a new GIRK1/2 activator with suitable properties. Abstract : The present study describes the discovery and characterization of a series of N -(1-(1, 1-dioxidotetrahydrothiophen-3-yl)-3-methyl-1 H -pyrazol-5-yl)acetamide ethers as G protein-gated inwardly-rectifying potassium (GIRK) channel activators. From our previous lead optimization efforts, we have identified a new ether-based scaffold and paired this with a novel sulfone-based head group to identify a potent and selective GIRK1/2 activator. In addition, we evaluated the compounds in tier 1 DMPK assays and have identified compounds that display nanomolar potency as GIRK1/2 activators with improved metabolic stability over the prototypical urea-based compounds.